ASEAN-GERMANY DIPLOMACY IN MARINE WASTE MANAGEMENT IN MANADO THROUGH 3RPROMAR (PROTECTING OCEANS & REEFS) 2023-2024 - Khuzaimah, Salfa; Firdaus, Aos Yuli; Indrayani, Irma; Syabudin, Doddy W. (Journal of Social Political Sciences, 2025)
Plastic waste pollution has emerged as a critical transboundary environmental issue, posing significant threats to marine biodiversity, coastal communities, and ecosystem services. This study investigates the role of environmental diplomacy in addressing marine plastic waste through the 3RProMar (Reduce, Reuse, Recycle – Protect the Marine Environment and Coral Reefs) Project implemented in Manado, Indonesia, during the period 2023–2024. Manado was strategically chosen due to its high vulnerability to plastic leakage into the marine environment and the surrounding coral reef systems. The research aims to assess the effectiveness of multilateral cooperation in mitigating marine plastic pollution by examining the implementation of 3RProMar, a collaborative initiative involving the Government of Indonesia, the Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ), and the Association of Southeast Asian Nations (ASEAN). Employing a qualitative research design, data were collected through content analysis of project documentation, semi-structured interviews with stakeholders, and an extensive review of relevant literature. The study identifies key challenges, including inadequate waste management infrastructure and limited public awareness. However, the findings indicate that the project has achieved significant progress through the integration of technological innovation, community education programs, infrastructure development, and capacity building. Notably, the initiative has contributed to a reported annual reduction of plastic waste by approximately 30% in the target area, alongside increased public engagement in sustainable waste practices. The research concludes that environmental diplomacy, when operationalized through inclusive, multistakeholder cooperation and context-specific interventions, can serve as an effective instrument for addressing marine pollution and promoting sustainable development in coastal regions.